EFFECTIVENESS OF PROBIOTIC, PREBIOTIC, AND SYNBIOTIC APPLICATIONS IN INCREASING FISHERY FARMING PRODUCTIVITY - Hasyimi, Wahid; Yandi, Misri (Jurnal Perikanan Unram, 2025)
Aquaculture is one of the important sectors that fulfill the community’s animal protein needs. However, the intensification of aquaculture often faces challenges such as decreasing water quality, increasing disease attacks, and suboptimal organism growth. To overcome these problems, biotechnology-grounded approaches such as the application of probiotics, prebiotics, and synbiotics have begun to be widely developed. Probiotics are living microorganisms that provide health benefits to the host by improving intestinal microflora, while prebiotics are non-digestible compounds that encourage the growth of beneficial microorganisms. The combination of the two, known as synbiotics, is believed to provide a synergistic effect in improving the health and resilience of aquatic organisms. This article reviews various research results related to the effectiveness of the use of probiotics, prebiotics, and synbiotics in improving growth performance, disease resistance, and feed efficiency in various fish and shrimp species. By implementing this strategy, sustainable aquaculture can be realized by strengthening the natural immune system and improving the balance of aquatic microbiota.